2015
DOI: 10.1139/apnm-2014-0560
|View full text |Cite
|
Sign up to set email alerts
|

Regular- and postseason comparisons of playing time and measures of running performance in NCAA Division I women soccer players

Abstract: The management of playing time in National Collegiate Athletic Association (NCAA) soccer athletes may be a key factor affecting running performance during competition. This study compared playing time and running performance between regular-season and postseason competitions during a competitive women's soccer season. Nine NCAA Division I women soccer players (age, 21.3 ± 0.9 years; height, 170.3 ± 5.7 cm; body mass, 64.0 ± 5.8 kg) were tracked using portable GPS devices across 21 games during a competitive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 33 publications
(53 reference statements)
4
62
2
Order By: Relevance
“…Interestingly, there was no impact of poor sleep on match demands in these players (Turczyn, 2018). In contrast to the impact of match schedule, no differences were observed for high-speed or sprint distances between NCAA Division I regular-season and playoff matches (Wells et al, 2015), suggestive that players were able to continue playing with similar intensity throughout an entire season. Overall, these studies highlight how contextual factors might impact game demands for female college soccer players and the need to monitor these metrics in order to manage the physical demands players experience during the season.…”
Section: Collegementioning
confidence: 73%
See 3 more Smart Citations
“…Interestingly, there was no impact of poor sleep on match demands in these players (Turczyn, 2018). In contrast to the impact of match schedule, no differences were observed for high-speed or sprint distances between NCAA Division I regular-season and playoff matches (Wells et al, 2015), suggestive that players were able to continue playing with similar intensity throughout an entire season. Overall, these studies highlight how contextual factors might impact game demands for female college soccer players and the need to monitor these metrics in order to manage the physical demands players experience during the season.…”
Section: Collegementioning
confidence: 73%
“…So, researchers tend to either include players that competed in full matches (which limits the sample size) or "create" 90-min matches from multiple players (which tends to alter movement rates). This is evident from a study comparing Division I regular season and post-season matches, which showed a 10% increase in total distance with a corresponding 6.5% decrease in movement rate (Wells et al, 2015). Nevertheless, total distances reported for NCAA Division I (∼9,000-9,900 m) (McCormack et al, 2014;Vescovi and Favero, 2014;Sausaman et al, 2019), Division II (∼10,000) (Gentles et al, 2018), Division III (∼9,600-9,800 m) (Jagim et al, 2020) as well as Canadian University matches (∼8,800-9,600 m) (Turczyn, 2018) are fairly similar, with subsequent movement rates of ∼100-110 m/min.…”
Section: Collegementioning
confidence: 96%
See 2 more Smart Citations
“…11 Increased risk of recurrent injury during postseason implies slightly different risk factors for recurrent injuries compared with primary injuries, which occur most often during regular season across all collegiate divisions. 20 Postseason often requires a different type of play, such as increased number of minutes played 41 and increased perceptual strain during similar work, 28 which may heighten the risk of recurrent ACL injury. Sports performance and medical staff may need to consider injury history during postseason.…”
Section: Discussionmentioning
confidence: 99%